The influence of thoroughbred racing on specific serum biochemistry parameters in racing horses in Selangor - Saidon, Mohamad Hafizi (2017)
Short duration high intensity thoroughbred racing causes the elevation of serum biochemistry parameters such as lactate, glucose, creatine kinase (CK), aspartate transaminase (AST)and alanine transaminase (ALT) in the serum. The lactate and glucoseare metabolic fuel of the muscles.CK, AST and ALT parameters are muscle-derived enzymes. This study was conducted to measure the influence of exercise to these parameters and to compare the increments of each categories. Blood was sampled from horses that won first and third placing.Method of blood collection was via jugular venipuncture shortly after the race. 36 horses were sampled from 18 thoroughbred track races, which distances range from 1100m, 1200m, 1300m, 1400m, and 1600m. Based on the study here, it was observed that the mean value for lactate had a substantial increase by approximately 30 folds. The mean value for AST, ALT, and glucose levels elevated two-folds. However, the mean value for CK is within normal range. The substantial increase of lactate could beexplained by muscles engaging in anaerobic glycolysis to compensate the high energy demand for high intensity racing in a short duration. CK remained within normal range with AST and ALT showing slight elevations indicating the enzymes were liver-derived which is normal for clinically fit horses post exercise. Physiologic hyperglycemia is caused by insulin-antagonistic actions of catecholamines, glucocorticoids, growth hormone, and glucagon. Statistical analysis suggested that changes between the first placing horse (Winning horse) and the third placing horse (Show horse) did not pose a significant difference between groups for all parameters so as the differences in distance, gender, and age. Lactate levels indicate the oxidative capacity of muscles in horses, so a higher level of lactate could indicate earlier engagement of anaerobic glycolysis. Future recommendations for similar study, suggest obtaining variables that are more differentiated such as between the winning horse and horses placed tenth instead. Determination of biochemistry level of lactate would reflect the anaerobic glycolysis of racing thoroughbred horses hence suggest indirect response to muscle fatigue.